Communication networks, organizational contacts and communication power in grooming professionals for career success - Wok, Saodah; Hashim, Junaidah (Universiti Kebangsaan Malaysia Press, 2014)
Networks, contacts and power are very important for career success. As such this article tries to (a) find out the use of social network sites for social and/or professional purposes, (b) examine the differences between the internal contact and the external contact used by employees, (c) ascertain the differences between information power and relational power used, and (d) analyze the relationships between communication networks, organizational contacts and communication power with career success. The study employed a quantitative research design. A total of 308 middle-level management officers were surveyed, using a questionnaire as the research instrument for data collection. Findings revealed that the employees used mainly email, Facebook and Twitter. They used social networking sites more for social networking than for professional networking. Generally, the employees used more of the internal contacts than the external contacts. However, the employees perceived that they were equally capable of having information power and relational power. Nonetheless, the findings also showed that career success was predicted by information power, external contacts, social networking use, and relational power. Therefore, career success encompasses both what you know and whom you know to climb up the career ladder for successful accomplishment at the workplace.